WAYANG KULIT MANUSIA ANTARA MITOS DAN KENYATAAN - Herum Marwoto, Otok (CORAK, 2012)
A religious traditional art in society is related to myth which can be categorized into folktale. This tradition has been often become one in the Javanese mind and influential in giving direction to their lives. Concerning with myth is inseparable from peopleâs believed. The people believe which is appearing is usually established on the basis of a tale or story, which is descendant from the local people and unwritten but believed by the society so that it becomes tradition and culture encouragement. One of Indonesian ancestorsâ heritages is leather puppet which can be enjoyed by us until now, although the form and the development conform to the development of the present modern world. Myth of the leather puppet in Javanese people themselves has been an icon, because the leather puppet it selves becomes myth which unified with tradition as well as Javanese people culture. So, other myth follows the leather puppet myth. One of the existing myths in society are the mythâs appearances of humanâs skin puppet, mainly a traditional art of leather puppet the material of which is believed to be created from humanâs skin. Kedakan village located in the slope of Merbabu valley which is remote and far from the city. Because of its remote location, this place leave culture heritage of the preserved ancestorâs tradition, such as humanâs skin puppet. The appearing myth in the human skin puppet is that of believed that the puppet is created from humanâs skin, therefore, the puppet is considered holy and highly respected. The sacredness of the puppet appears, since many misterious and illogical things happened related to the sacred puppet frequently. The myth which are still being preserved enables this leather puppet art in the remote village ever lasting and the existence is still being nurtured. Key words: Leather Puppet, Human Skin, and Myth